In vivo effect of interleukin-1beta and interleukin-1RA on oocyte cytoplasmic maturation, ovulation, and early embryonic development in the mare - Gérard Nadine; Duchamp Guy; Caillaud Maud (BMC, 2005)
Abstract A growing body of evidence suggests that the interleukin-1 system is involved in periovulatory events. Previous work from our lab demonstrated that in the mare, interleukin-1beta (IL-1beta) increases the ovulatory rate of metaphase II oocytes. The present study was conducted to analyze in vivo the effect of IL-1 on oocyte cytoplasmic maturation, ovulation and pregnancy rate. In the present work, IL-1beta (experiment 1, n = 13; experiment 2, n = 25) and interleukin-1RA (IL-1RA; experiment 1, n = 25) were injected intrafollicularly by using the transvaginal ultrasound-guided injection method. Injections were performed on cyclic mares when the diameter of the growing dominant follicle reached 30-34 mm. In experiment 1, mares were inseminated the day of the treatment and all the other day until ovulation. The time of ovulation was determined and a pregnancy diagnosis was performed 14 days after ovulation of the injected follicle. In experiment 2, the cumulus-oocyte complex from each injected follicle was collected by transvaginal ultrasound-guided aspiration 38 h after the intrafollicular injection. Oocyte nuclear stage and oocyte cytoplasmic maturation were assessed by analyzing chromatin configuration, cortical granules migration and mitochondria distribution under a confocal microscope. The results from experiment 1 confirm that an intrafollicular injection of 1 microgram IL-1beta induces ovulation in the mare whereas IL-1RA has no effect at the dose used in the present study. Furthemore, we demonstrated, that in our experimental conditions, IL-1beta and IL-1RA induced a decrease in embryo development. Experiment 2 leads us to observe that IL-1beta is unable to induce cortical granules migration and remodelling of mitochondria, that commonly occurs during oocyte maturation, whereas it acts on nuclear maturation. This result may explain the decrease in embryo development we observed after IL-1beta intrafollicular injection. In conclusion, the present study tends to demonstrate that IL-1beta plays a role in the ovulatory process and may acts on oocyte maturation in the mare, but additional factors are required to complete equine oocyte cytoplasmic maturation to allow embryo development.